Optimisation of bio-based building materials using image analysis method. (30th October 2019) - Brás, Ana; Antunes, Ana; Laborel-Préneron, Aurélie; Ralegaonkar, Rahul; Shaw, Andy; Riley, Mike; Faria, Paulina
Highlights: Bio-based materials are examined in terms of 2D image analysis. Influence of casting on biofibres dispersion in bio-based insulation materials. Bio-composites made with barley straw, hemp shiv and rice husk fibres were produced. Production variables have a significant impact on the physical properties. Abstract: Wetting of bio-based mortars — the affinity of the biofibres and earth to the water — can have a strong impact on the flow, but the microscale physics and macroscopic consequences remain poorly understood, not helping in the material optimisation. This research analyses the influence of casting on biofibres dispersion in bio-based insulation materials at the macro-level and evaluate changes on hygrothermal behaviour if fibres and casting change. Earth-based blocks reinforced with 3% weight content of barley straw, hemp shiv and rice husk fibres were produced with 5 and 4 cm thickness using two casting methods. The 5 cm blocks were unstabilised and compacted; the 4 cm blocks were moulded and stabilised with gypsum and air lime. The approach is to implement a developed method of image analysis to elucidate the inherently 2D pore-scale mechanisms and help explain the striking macroscopic displacement patterns that emerge. The results indicate that production variables have a significant directionally dependent impact on the physical properties of cast bio-based materials. This means that the Image analysis can be used for quality control towards the optimisation of the bio-composites. Thermal conductivity and ultra sound velocity are affected by fibres distribution inside bio-based materials. The shape of ultra sound distribution from direct and indirect methods enhance the anisotropy of the bio-based materials with different composition and casting methods.